Measuring Fun: A Case Study in Adapting to the Evolving Metrics of Player Experience - Strubberg, Brandon C.; Elliott, Timothy J.; Pumroy, Erin P.; Shaffer, Angela E. (Loading, 2020)
The gaming industry and the concept of gamification have altered the way many developers and users approach interactive products. As social gaming demographics expand to what was previously considered “casual” audiences, more users expect an enjoyable experience from their digital applications and games. Developers now request more detailed subjective descriptions of satisfaction and the player experience from user-experience (UX) practitioners. Focusing on how fun a product is for users/players requires subjective, situationally dependent metrics rather than traditional UX efficiency metrics. The UX discipline is still constructing a comprehensive ecology of the player experience and how to measure it. This article contributes to that ecology by detailing a case in which our team conducted a usability test on a new video game peripheral. Our client’s primary concern dealt with how fun experienced gamers found the device. As our test progressed, we encountered a number of fun-related participant behaviors that led us to develop new metrics beyond our initial planned metrics. These new metrics helped us and our client better define and discuss enjoyability. Our case, in conjunction with a detailed definition and review of player experience and UX scholarship, shows the importance of adopting metrics contextually specific to the video-game product and player group when measuring fun is the primary goal.